Evaluate the Association between Platelet to Lymphocyte Ratio and the Clinical and Histological Properties in Nonmetastasis Colorectal Cancer Patients - عبد الله, نادر; ريه, مي (Latakia University Journal -Medical Sciences Series, 2021)
Cancer is an important global health issue, and colorectal cancer is one of the most common cancers worldwide. It was recently discovered that the systemic inflammatory response plays a supportive role in various types of cancer, including colorectal cancer. The inflammatory response can be reflected by several indexes, including the platelet lymphocyte ratio (PLR).Cancer is an important global health problem, and colorectal cancer is one of the most common cancers. In contrast, the systemic inflammatory response has a warning role in many types of cancer, including colorectal cancer. The inflammatory response can be evaluated with several indicators, including the platelet lymphocyte ratio PLR. يعد السرطان مشكلة صحية عالمية مهمة ، وسرطان القولون والمستقيم هو أحد أكثر أنواع السرطان شيوعًا. في المقابل ، فإن الاستجابة الالتهابية الجهازية لها دور تحذيري في العديد من أنواع السرطان ، بما في ذلك سرطان القولون والمستقيم. يمكن تقييم الاستجابة الالتهابية من خلال عدة مؤشرات ، بما في ذلك نسبة الصفائح الدموية اللمفاوية PLR. Cancer is an important global health problem, and colorectal cancer and colorectal cancers, the most common ", in contrast to be inflammatory response to the systemic role of sentinel in many cancers, including cancer of the colon and rectum. Can evaluate the inflammatory response in several indicators, including the proportion of antiplatelet lymphocytes Platelet Lymphocyte Ratio PLR)) يعتبر السرطان مشكلة صحية عالمية مهمة ، وسرطان القولون والمستقيم وسرطان القولون والمستقيم هما الأكثر شيوعًا "، على عكس الاستجابة الالتهابية للدور الجهازي للحارس في العديد من السرطانات ، بما في ذلك سرطان القولون والمستقيم. يمكن تقييم الاستجابة الالتهابية في عدة مؤشرات ، بما في ذلك نسبة الخلايا الليمفاوية المضادة للصفيحات الصفائح الدموية Lymphocyte Ratio PLR)) Can't load full results Try again Retrying... Retrying... Our study aimed to evaluate the relation between platelet lymphocyte ratio and to correlate this ratio with the clinicopathological characteristics of non-metastatic colorectal cancer patients. We enrolled 95 non-metastatic colorectal patients at Oncology Depatment at Tishreen University Hospital. Our results revealed that there were statistically significant differences in the higher mean of lymphocyte platelets ratio by the stage of the tumor (p<0.0001), by the size of the tumor (p=0.001), and by the metastases of the lymph nodes (p=0.03), as the mean increases with the tumor stage with the size of the tumor and the formation of metastases in the lymph nodes. While there were no statistically significant differences in the higher mean of lymphocyte platelets by the histological grade of tumor (p = 0.1), as well as by the tumor location in the left and right colon (p= 0.3). These results reflect the correlation of the high percentage of lymphocyte platelets with the histopathological clinical characteristics that indicate a poor prognosis in patients with colorectal cancer